Predictors of psychological well-being among high school teachers: A cross-sectional study from Southern India - Rajesh, chinthana; Ashok, Lena; Rao, Chythra R; Kamath, Veena; Kamath, Asha; Chandra Sekaran, Varalakshmi (Indian Journal of Community Health, 2020)
Background: Well-being is increasingly emerging as an important determinant of teacher effectiveness. Aim and objective: To assess the predictors of psychological well-being in Southern India. Settings and design: A cross-sectional study was conducted among 460 high school teachers from government and private schools in Udupi district. Methods and materials: Ryff’s psychological well-being scale (1989) was used. Statistical analysis used: Predictors were identified using logistic regression and p<0.05 was considered to be statistically significant Results: Autonomy, personal growth, positive relations, purpose in life and self-acceptance emerged as predictors of psychological well-being. Age predicted the subdomain of autonomy; number and age of children predicted environmental mastery; gender, monthly income and travelling time of teachers predicted the subdomain of self-acceptance among teachers. Conclusion: Teachers are an important resource whose psychological well-being has not received the attention it is due. An intervention program designed to fit their felt needs may be a step in the right direction.